Monoclonal Antibody AP3 Binds Galactomannan Antigens Displayed by the Pathogens Aspergillus flavus, A. fumigatus, and A. parasiticus - Schubert, Max; Xue, Sheng; Ebel, Frank; Vaggelas, Annegret; Krylov, Vadim B.; Nifantiev, Nikolay E.; Chudobová, Ivana; Schillberg, Stefan; Nölke, Greta (Frontiers in Cellular and Infection Microbiology, 2019)
Aspergillus fumigatus and A. flavus are fungal pathogens linked to most cases of invasive aspergillosis (IA). Early detection of the circulating antigen galactomannan (GM) in serum using specific antibodies allows the prompt application of effective antifungal therapy, thus improving the survival rate of IA patients. The use of known mAbs in the IA diagnosis is often associated with false positive results due to cross-reactivity with some bacterial polysaccharides , that challenge the search of more specific mAbs. Here we describe the characterization of the Aspergillus-specific monoclonal antibody (mAb) AP3 (IgG1κ), including the identification of its specific target antigen. The antibody was generated using A. parasiticus cell wall fragments and was shown to bind specifically to Aspergillus spp. Immunofluorescence microscopy revealed the presence of the target antigen in the cell wall. However, the analysis of culture media by immunoprecipitation and ELISA showed that the antigen was also secreted into the medium. The inability of AP3 to bind the A. fumigatus galactofuranose (Galf)-deficient mutant ΔglfA confirmed that Galf residues are part of the epitope. Several lines of evidence strongly indicate that AP3 recognizes Galf residues linked to O-glycans on Aspergillus proteins. A glycoarray demonstrated that mAb AP3 could effectively recognize oligo-[β-D-Galf-1,5]-sequences starting from a tetramer while longer chains are recognized more efficiently. Moreover, AP3 captured GM in the serum, suggesting that this antibody may be a useful tool for the diagnosis of IA.